Association of Breast Feeding and Birth Weight with Anthropometric Measures and Blood Pressure in Children and Adolescents: The CASPIAN-IV Study - Shirin Djalalinia; Mostafa Qorbani; Ramin Heshmat; Mohammad Esmaeil Motlagh; Gelayol Ardalan; Nima Bazyar; Majzoubeh Taheri; Hamid Asayesh; Roya Kelishadi (Elsevier, 2015)
Noncommunicable diseases (NCDs) and their risk factors are major health threats especially for developing countries. The aim of this study was to assess the association between breast feeding (BF) and birth weight (BW) with anthropometric measures and blood pressure (BP) in a nationally-representative sample of Iranian children and adolescents. Methods: In this national survey, 14,880 children and adolescents, aged 6-18 years, were selected using a multistage, cluster sampling method from rural and urban areas of 30 provinces of Iran. BF duration and BW were assessed by validated questionnaires completed by parents. Results: The study participants were 13,486 students (participation rate of 90.6%). They consisted of 49.24% girls, 75.6% urban residents, with a mean age of 12.5 years (95% confidence interval: 12.3-12.6). The family history of obesity had a significant association with BW (p < 0.001). A substantial association was found between BF duration and the order of children in the family, both in boys (p < 0.001) and girls (p < 0.001). The mean values for height, weight, body mass index, as well as waist, wrist, and hip circumferences were higher in those with higher BW categories (p for trend < 0.001). As BW increased, there was a linear decrease in underweight (p for trend < 0.001) and a linear increase in the prevalence of generalized obesity (p for trend < 0.001) was documented. Conclusion: BW was associated with a higher prevalence in general obesity and a lower prevalence of being underweight. Duration of BF had no significant association with anthropometric measures and BP. Future longitudinal studies are necessary to determine the clinical implications of these findings.